Analisis Pengendalian Persediaan Barang Dagang (Inventory) Dan Harga Pada Keputusan Pembelian Air Minum Dalam Kemasan (Amdk) Merek Isqo PT Metro Surya Inovasi (PT Mesva) Di Kota Metro Lampung - Ruswanti, Lilis; Nusantoro, Jawoto; Kurniawan, Angga (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This research is a qualitative research with a qualitative descriptive method. This study took 1 respondent from the warehousing staff of PT Metro Surya Innovation as a provider of information about the company's merchandise inventory and 6 large outlets selling Isqo brand bottled drinking water as a provider of price information on purchasing decisions for isqo brand bottled drinking water. Data collection techniques using observation, interviews, and documentation. Based on the results of the analysis and assessment in this study, it shows that in the period August-December 2021, the EOQ/KPE method is 999 units/box with a repurchase frequency of 14 times. Safety stock is 95 units/box and ROP/TPK 190 units, the maximum inventory of goods at the company that must be maintained is 1,094 per day. Based on the comparison results if the merchandise control method is carried out using the EOQ/KPE method, the company can increase efficiency and provide benefits to the company with a cost difference of Rp. 7,281,281. The results show that by using the EOQ/KPE method, the company can precisely determine the safety stock so as to minimize the occurrence of shortages of goods and can also determine the ROP/TPK to avoid delays in ordering and delivery of goods to the customer.